Ngenger Tradition as Informal Education in Muhammadiyah Cultural Adaptation - Darwis, Aulia Fathurrahman; Wildan, Muhammad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Informal education has long played a central role in transmitting religious values and character formation within Islamic communities. Specific Background: In Javanese society, the ngenger tradition—living with and serving a foster family—functions as experiential learning through daily interaction and role modeling. Knowledge Gap: However, its role in connecting traditional Islamic environments with Muhammadiyah’s modernist orientation remains underexplored. Aims: This study examines how the ngenger tradition operates as a medium of informal education and cultural adaptation in the transformation of religious orientation from traditional or abangan Islam toward Muhammadiyah in Tempurejo (Ngawi) and Grogol (Ponorogo). Results: Using a qualitative historical approach and Cultural Adaptation theory, the findings show that participants internalized Muhammadiyah values through everyday practices and later reproduced them through community religious activities, educational initiatives, and institutional development in Grogol. Novelty: The study reveals that ngenger functions as a culturally embedded mechanism linking experiential learning with ideological transformation. Implications: These findings demonstrate that local traditions can facilitate the integration of modern Islamic organizational values within rural communities through adaptive and minimally conflictive cultural processes. Highlights: Experiential learning through residential service relationships facilitated gradual internalization of Muhammadiyah religious and organizational values. Returning participants transmitted newly acquired religious practices and social norms through community religious gatherings and educational initiatives. Local institutional development—including mosques and schools—emerged from the value reproduction processes carried by former participants. Keywords: Ngenger, Informal Education, Cultural Adaptation, Muhammadiyah